ANALISIS TRANSFORMASI EKONOMI DAN DISPARITAS PEMBANGUNAN ANTAR KECAMATAN DI KABUPATEN DONGGALA PASCA PEMEKARAN TAHUN 2008 - Wibowo, Indra Prasetyo (Katalogis, 2017)
This research was conducted in Donggala Regency, which has experienced twice the regional growth in less than a decade. This research aims to determine the magnitude of economic transformation and their growth patterns, the distance disparities among district development and the significance of the difference post-expansion area. To reveal the magnitude of economic transformation used contribution analysis tool, while the growth patterns using Klassen Typology. The measurement of development disparities used Williamson Index and Taxonomic Method, while Wilcoxon Signed Rank Test to see the significance of disparity differences among periods. Contribution analysis showed the economic transformation along with the changes in the dominance of the economic structure from the primary sector to the tertiary sector reaching 43,53 percent in 2014, while the Klassen Typology showed an increase in economic growth and Gross Regional Domestic Product (GRDP) per capita above average in Banawa and Damsol. Williamson Index changes from 0,094 become 0,144 in 2014, indicates a trend of increased development disparities, while the Taxonomic Method which measures development with broader dimensions discover the improvements of development disparities in some districts. The results of Wilcoxon Signed Rank Test with a confidence level of 95 percent concluded that there was no significant difference in the development disparities among periods.Â